SOMACLONAL PUTATIVE MUTANTS OF RICE TOLERANT TO SALINITY - Rossa Yunita; Nurul Khumaida; Didy Sopandie; Ika Mariska (Indonesian Agency for Agricultural Research and Development, 2018)
Soil salinity could significantly reduce rice yield, therefore, varieties tolerant to salinity are urgent to be developed. Mutation induction could be used to create rice mutants tolerant to salinity. The study aimed to evaluate the tolerance of somaclonal mutants of rice to NaCl salinity in a greenhouse condition and characterize their tolerance mechanism. A total of 45 putative mutants were generated by a gamma ray mutation induction followed with in vitro selection in the growth media containing different NaCl concentrations in the greenhouse experiment. The study consisted of two-factor treatments, namely three levels of NaCl concentrations and 45 rice mutants suspected to be tolerant to salinity, arranged in a completely randomized design. Proline, cations (K, Na, Ca, and Mg) content, and stomata density were evaluated. The results showed that eight mutants were tolerant to 150 mM NaCl, namely CH30, CH-4-2, II-13-42, II-13-7, II-13-10, II-13-13, II-13- 2, and IA-3-21. These tolerant mutants had a higher Na content compared to the check parent. The tolerant mutants had a high proline content, lower Na, and stable K, Mg and Ca cations as well as had a greater number of stomata and higher stomata length-width ratio. Some of the identified tolerant mutants demonstrated the tolerant mechanism against salinity stress. Further studies are required to evaluate these tolerant mutants in the field conditions under salinity stress.